Non-conservative forces in bulk systems. Issue 12 (13th August 2017) - Todorov, Tchavdar N.; Cunningham, Brian; Dundas, Daniel; Horsfield, Andrew P.
ABSTRACT: The ability of electrons and phonons to equilibrate is fundamental to the thermodynamic and transport properties of solids. Nonetheless in mesoscopic systems, sufficiently high current densities can lead to situations where the phonon subsystem can no longer reach a steady state. In previous work, this phenomenon was connected with the demonstration that interatomic forces under current are non-conservative, with dramatic dynamical effects. Here we consider these effects in bulk systems. We arrive at a critical current density beyond which current flow results in the uncompensated stimulated emission of a blast of phonons. The result is illustrated with simulations of long atomic wires. It is hoped that the paper will stimulate research into the possible relevance of the effect to electropulsing. This paper is part of a themed issue on Materials in External Fields.